Kajian Desain Struktur Balok Pada Gedung Bertingkat Berdasarkan SNI 2847:2013 pada Gedung Menara BRI Medan - Yusrizal Lubis; Diana Suita (Jurnal Simetri Rekayasa, 2021)
The BRI Medan Tower Building is a multi-storey building consisting of 12 floors and 2 basements, so that in planning the structure it must be designed to be strong and safe enough to withstand the load carried and withstand external influences on the structure. Previously, the BRI Medan Tower Building was a building with old design standards. Thus, this thesis aims to evaluate the design of beam structures in existing buildings based on SNI 2847:2013 concerning Requirements for Structural Concrete for Buildings. The method used is the beam analysis method using SNI 2847:2013. From the analysis results, it is found that the evaluation of beam analysis calculations obtained with the results in the field is the same. The installed compression reinforcement has not yielded so that the beam cross section is a tension controlled section. The flexural reinforcement distance in the beam is D10-200. The results of the evaluation of the beam analysis calculation obtained the amount of tensile reinforcement 14D25 and 4D25 and compression reinforcement 12D25 has been able to carry the load on the beam, so it can be concluded that the results of the planning have met the applicable requirements. SNI 2847:2013 can be used for planning reinforced concrete structures because the results obtained at the time of planning with the results in the field are the same.